INCIDENCE OF POST-OPERATIVE DEEP VEIN THROMBOSIS IN PATIENTS WITH LOWER LIMB OPEN FRACTURE - Adnan Husain, Hnoosh (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Venous thromboembolic (VTE) disease with i t ' s h i g h morbidity and mo r t a l i t y is currently one of the most serious postoperative complication, (DVT) can lead tofatal pulmonary embolism (PE). or the development of post thrombotic syndrome.Patients and methods: This is a prospective study which was carried on 85 patients had s i n g l e lower l i m b open fracture with no other major i n j u r i e s in other sites of body(with the exception of superficial wounds or b r u i s e s ) .They were d i v i d e d i n t o groups according to age, gender, weight, type of fracture, methods of immobilization, duration ofh o s p i t a l i z a t i o n , duration of operation. All the patients including asymptomatic patients were subjected by the fourth postoperative day for duplex untrasonography study.Results: The total number of patients with DVT that documented by Duplex study was 27 patients with in incidence of (31.76%), the incidence of DVT is higher in proximal lowerextremity fractures as around hip (45.45%) Versus (12.5%) in lower tibial fractures. the incidence of DVT increased with increasing severity of open fracture; (50% in Gus t i l o type IIIB. 10% in Gus t i l o type I).Conclusion: Age, weight, female gender, and severe open fracture proximal part of the lower limb, long hospitalization, prolong surgery are risk factors in the development of (DVT).